2016
DOI: 10.1051/matecconf/20167400033
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fiber Reinforced Composites: A Review on Potential for Corrugated Core of Sandwich Structures

Abstract: Abstract. Natural fibers, characterized by sustainability, have gained a considerable attention in recent years, due to their advantages of environmental acceptability and commercial viability. In this paper, the characterization of natural fibers including the mechanical properties and alkalization of fibers is presented. Most recent study had gone through the mercerization process to improve the toughness of natural fibers; which is a well-known hydrophilic material. Traditional reinforcement method was comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Manipulating the core material and its design can change the behavior of the sandwich structure, both in terms of compression and impact properties. For example, Jusoh et al [ 100 ] stated that more experimental works should be conducted on corrugated core sandwich structures made of natural fibers. It is evident that, based on the information in the literature, the type of core material can significantly alter the overall properties of the composite.…”
Section: Mechanical Properties Of Nfcs Core Sandwich Structuresmentioning
confidence: 99%
“…Manipulating the core material and its design can change the behavior of the sandwich structure, both in terms of compression and impact properties. For example, Jusoh et al [ 100 ] stated that more experimental works should be conducted on corrugated core sandwich structures made of natural fibers. It is evident that, based on the information in the literature, the type of core material can significantly alter the overall properties of the composite.…”
Section: Mechanical Properties Of Nfcs Core Sandwich Structuresmentioning
confidence: 99%
“…Nikbakt et al 31 presented a review of optimization studies on composite structures by representing a classification based on the type of structures. Jusoh et al 32 summarized the characterization and researches of natural fibers-reinforced composites to create corrugated core for sandwich structures. Zaid et al 33 proposed a review of sandwich structure based on corrugated core.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the specific strength of the sisal-PP honeycomb cores is almost twice higher than that offered by the pure PP honeycomb cores. Jusoh et al [12] reviewed the natural fiber composites as potentially used for corrugated core structures. Du et al [13] stated that skins made of biofiber based paper-reinforced polymer showed comparable flexural properties to the glass fiber reinforced polyurethane skins.…”
Section: Właściwości Mechaniczne Pod Obciążeniem Quasi-statycznym Rdzmentioning
confidence: 99%